Assessing the Transparency and Compliance of Procurement Processes in Kitwe City Council: A Study of Goods and Services - Clifford Sikanyiti; Kelvin Chibomba (Journal of Arts, Humanities and Social Science, 2025)
Transparency and compliance in the procurement process is vital for the financial sustainability and developmental progress of Kitwe City Council. The rationale behind this research was to establish the Transparency and compliance of procurement processes in Kitwe City Council, the case study of goods and services. The primary objectives of this study were threefold: To establish the procurement processes in in Kitwe City Council, to determine the Transparency and compliance of procurement processes in in Kitwe City Council, and to ascertain the challenges of procurement processes in in Kitwe City Council. The population for the study was 50 respondents both from Kitwe City Council and suppliers. The descriptive research design was employed because it is suitable for gathering qualitative and quantitative information. Simple random sampling was adopted to select members of the procurement committee and staff from various departments in the council. The data collection methods included primary and secondary data collection. Different data analysis techniques such as modeling to reach trend relationship were used. This approach provided a comprehensive assessment of the procurement process systems and their impacts on Kitwe City Council. The results of this study identified weaknesses the procurement management system. There is a need to review the structural and operational frameworks governing Kitwe City Council procurement process, tighten procurement staff training, strengthen legislative oversight and public audit functions, loose areas in procurement frameworks, institute transparency. The implications of this research are significant, contributing to a better understanding of how transparency and compliance in procurement can enhance the value for money.